2022
DOI: 10.1182/bloodadvances.2022007693
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal study of glomerular hyperfiltration in adults with sickle cell anemia: a multicenter pooled analysis

Abstract: Glomerular hyperfiltration is common in young sickle cell anemia (SCA) patients and precedes development of overt kidney disease. In this multicenter pooled cohort, we characterized hyperfiltration and its decline to normal range in adult patients. Glomerular filtration rate (GFR) was estimated using the creatinine-based 2009 CKD-EPI equation omitting race adjustment and the 2021 CKD-EPI equation. Using CKD-EPI-2009, 506 patients had baseline eGFR ≥90 mL/min/1.73 m2, median age of 24 (IQR: 19, 34) years and 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…The new equations slightly underestimate eGFR in African Americans and overestimate it in the general population. The new creatinine-cystatin C equations without race were more accurate than new 10.3389/fmed.2022.1029224 creatinine equations, with smaller differences between race groups (21,80). Also, because the tubular secretion is the predominant mode of creatinine excretion when the GFR is less than 40 ml/min/1.73 m 2 , serum creatinine levels will produce false values in assessing GFR in older SCD patients with reduced metabolism and tubular dysfunction (36,76,81,82).…”
Section: Estimated Glomerular Filtration Rate Calculation Methodsmentioning
confidence: 79%
See 2 more Smart Citations
“…The new equations slightly underestimate eGFR in African Americans and overestimate it in the general population. The new creatinine-cystatin C equations without race were more accurate than new 10.3389/fmed.2022.1029224 creatinine equations, with smaller differences between race groups (21,80). Also, because the tubular secretion is the predominant mode of creatinine excretion when the GFR is less than 40 ml/min/1.73 m 2 , serum creatinine levels will produce false values in assessing GFR in older SCD patients with reduced metabolism and tubular dysfunction (36,76,81,82).…”
Section: Estimated Glomerular Filtration Rate Calculation Methodsmentioning
confidence: 79%
“…Early studies demonstrated that glomerular changes in SCD patients are characterized by high renal blood flow and glomerular hyperfiltration and hypertrophy, starting in infancy and declining to a normal range during the first two decades of life (18)(19)(20)(21)(22). Glomerular hyperfiltration is defined as estimated glomerular filtration rate (eGFR) above 130 ml/min/1.73 m 2 for women and 140 ml/min/1.73 m 2 for men.…”
Section: Hyperfiltration In Children and Fast Decline Of Glomerular F...mentioning
confidence: 99%
See 1 more Smart Citation
“…Glomerular filtration rate was estimated using the 2021 creatinine‐based Chronic Kidney Disease Epidemiology Collaboration (CKD‐EPI) equation 8 . Hyperfiltration was defined as eGFR >130 mL/min per 1.73 m 2 for women and >140 mL/min per 1.73 m 2 for men 9 . The study was approved by the University of Tennessee Health Science Center (UTHSC) at Memphis Institutional Review Board.…”
Section: Methodsmentioning
confidence: 99%
“…8 Hyperfiltration was defined as eGFR >130 mL/min per 1.73 m 2 for women and >140 mL/min per 1.73 m 2 for men. 9 The study was approved by the University of Tennessee Health Science Center (UTHSC) at Memphis Institutional Review Board. All participants gave written informed consent.…”
Section: Study Design and Participantsmentioning
confidence: 99%